2008
DOI: 10.1002/eji.200838449
|View full text |Cite
|
Sign up to set email alerts
|

Nramp1‐functionality increases iNOS expression via repression of IL‐10 formation

Abstract: In mice, resistance to certain intracellular microbes depends on the expression of a late phagosomal protein termed natural‐resistance associated macrophage protein 1 (Nramp1, Slc11a1). Nramp1‐functionality is associated with alterations of cellular iron homeostasis and a sustained pro‐inflammatory immune response, including the formation of the antimicrobial effector molecule NO. To investigate the underlying mechanism we used RAW‐264.7 murine macrophage cells stably transfected with a functional Nramp1 allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 46 publications
6
41
0
Order By: Relevance
“…Namely, lowering intracellular heme-iron in macrophages promotes the induction of NOS2, TNF, IL-6, IL-12 and histocompatibility (MHC) class II expression in response to IFNγ, an effect mediated in part by NRAMP1 (Fritsche et al, 2008) and involving the transcription factors HIF1α, nuclear factor for IL-6 (NF-IL6) and STAT family of transcription factors (Soares and Weiss, 2015). …”
Section: Macrophage Heme-iron Metabolism and Resistance To Infectionmentioning
confidence: 99%
“…Namely, lowering intracellular heme-iron in macrophages promotes the induction of NOS2, TNF, IL-6, IL-12 and histocompatibility (MHC) class II expression in response to IFNγ, an effect mediated in part by NRAMP1 (Fritsche et al, 2008) and involving the transcription factors HIF1α, nuclear factor for IL-6 (NF-IL6) and STAT family of transcription factors (Soares and Weiss, 2015). …”
Section: Macrophage Heme-iron Metabolism and Resistance To Infectionmentioning
confidence: 99%
“…The Nramp1 transporter is an intracellular protein that is recruited to the endosome, where it functions as a transporter for divalent cations, including Fe 2ϩ and Mn 2ϩ (39). There are several ways this transporter is thought to impact Salmonella survival, including denying the bacterium access to iron and activating inflammatory responses such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) (40)(41)(42). For susceptible (Nramp1 S ) mice, infection via the orogastric route leads to a systemic infection and is ultimately lethal in several days or up to 2 weeks (depending on the dose).…”
Section: Systemic Infection Small Animal Modelsmentioning
confidence: 99%
“…Using the murine macrophage cell line RAW264.7, it was observed that Nramp1 expression in macrophages can be further upregulated by exposure of these cells to both bacterial lipopolysaccharide and interferon-γ (IFN-γ), as well as to other inflammatory stimuli [22,23]. In addition, a macrophage cell line stably transfected with functional Nramp1 infected with Salmonella typhimurium produced more TNF-α than those with non-functional Nramp1, which accelerated the activity of antimicrobial effector mechanisms [23,24,25]. These differences between the present and previous studies, however, are not easily explained.…”
Section: Discussionmentioning
confidence: 99%